Current research in microbial sciences (Elsevier B.V, 2020)
"Current Research in Microbial Sciences publishes original papers and short communications, review articles as well as graphical reviews that cover all aspects of the broad field of microbiology, the study of microorganisms, or microbes, a diverse group of unicellular organisms and subcellular genetic material, and their biological interactions with human beings and other life. ... Current Research in Microbial Sciences topics covered include: Genetics, metabolism: bacteria, fungi, protozoa, viruses; Environmental microbiology; Host-microbe interactions; Antimicrobials; Microbial systems biology; Biofilms; Microbiota"--Publisher
Keywords: Microbiology : Periodicals; Microbiology; Microbiology; Microbiologie : Périodiques; Microbiologie; microbiology